New Sources of Eastern Filbert Blight Resistance and Simple Sequence Repeat Markers on Linkage Group 6 in Hazelnut (Corylus avellana L.) - Komaei Koma, Golnaz; Şekerli, Merve; Snelling, Jacob W.; Mehlenbacher, Shawn A. (Frontiers in Plant Science, 2021)
Commercial production of hazelnut (Corylus avellana) in Oregon's Willamette Valley is threatened by eastern filbert blight (EFB), a serious canker disease caused by the pyrenomycete Anisogramma anomala (Peck) E. Müller. The fungus also prevents the establishment of hazelnut orchards in eastern North America. Genetic resistance is considered the most effective way to control the disease. A high level of EFB resistance, first discovered in 'Gasaway', is conferred by a dominant allele at a single locus on linkage group 6 (LG6). Resistance from several additional sources has been assigned to the same chromosomal region. In this study, new simple sequence repeat (SSR) markers were developed for fine mapping the resistance region on LG6 and new sources of resistance were investigated. Forty-two new SSR markers were developed from four contigs in the genome sequence of 'Jefferson' hazelnut, characterized, and nine of them were placed on LG6 of the genetic map. Accessions representing 12 new sources of EFB resistance were crossed with susceptible selections resulting in 18 seedling populations. Segregation ratios in the seedling populations fit the expected 1:1 ratio for 10 sources, while one source showed an excess of resistant seedlings and another showed an excess of susceptible seedlings. Based on co-segregation of disease response and SSR marker scores in the seedlings, eight resistance sources were assigned to LG6 in the same chromosomal region as 'Gasaway' resistance. Linkage maps were constructed for each progeny using SSR markers. The LG6 resistance sources include two selections (#23 and #26) from the Russian Research Institute of Forestry and Mechanization near Moscow, four selections from southern Russia, one selection (OSU 1185.126) from Crimea, one selection (OSU 533.129) from Michigan, Corylus heterophylla 'Ogyoo' from the Republic of Korea, and the interspecific hybrid 'Estrella #1'. These new LG6 resistance sources and SSR markers should be useful in breeding new cultivars, including the pyramiding of resistance genes. For the other four resistance sources (Moscow #37, hybrid selection OSU 401.014, C. americana 'Winkler' and C. americana OSU 366.060), and SSR marker scores on linkage groups 6, 7 and 2 were not correlated with disease response.